(untitled) (Research, Society and Development, 2020)
Objective: to analyze the literature regarding the emotional and psychological suffering of nursing professionals during the pandemic. Methodology: this is an integrative review in which a survey of articles published in the databases of Latin American and Caribbean Literature in Health Sciences (LILACS), from the National Library of Medicine of the National Institute of Health of the United States, was carried out. (PubMed) and the Virtual Health Library (VHL), in 2020. Results and Discussion: in view of the studies analyzed, it was identified that nursing professionals are exposed to long working hours, insecurity in the face of illness, fear of contamination due to scarcity of PPE, lack of equipment and training to care for the infected patient. Still, it was noticed that the distance from the family is a factor that leads to the physical and mental illness of these professionals. Final considerations: the study makes it possible to reflect on the need for multiprofessional strategies that enable the creation of emotional stability, in addition to the creation of public policies that take into account the mental health of health teams, as well as the creation of tools to help exchange experiences used by professionals to manage emotions during the pandemic, through sensitive listening and maintenance of quality of life at work.